P-217 Paediatric palliative care transition – a service evaluation of support for teenagers with life-limiting conditions in south wales. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Watson, Rachel; Warlow, Timothy; Baba, Megumi
Abstract : Background: With the increasing survival of children with life-limiting conditions, support through teenage years and into adult services is of vital importance to children and families. The All Wales Paediatric Palliative Care Team has identified the need to implement a robust transition service. Aims: Undertake a two stage service evaluation of transition support in South Wales: 1) An audit of current provision against national transition guidance from NICE (2016) and Together for Short Lives (2015) 2) A qualitative assessment of the transition process by staff and families. Method: A retrospective notes audit was completed using hospice and hospital records. Care provided for 20 patients of transition age (14–17 years), and 10 patients post transition (18+) was assessed. Semi-structured interviews were conducted with eight families and 17 staff working with transition patients in a variety of roles. Results: For 25% of families, transition was the main concern they had when considering their child's future. During transition planning, all families had their ethical and cultural needs considered, with family wishes/aspirations for adulthood recorded in 63% of cases. 13% had documented goals for transition. There was no documented support for developing identity/sexuality/relationships, or spiritual development. By transition age, 37% had their needs met by an appropriate adult service. Two-thirds of families felt well supported during their transition. 67% felt poorly informed regarding adult services, despite 80% having met a member of adult palliative care team. No patients had a formal transition plan. 50% of staff felt support for transition was inadequate, with 70% expressing the need for improved continuity in the service. Conclusion: A clear transition process is required to ensure early planning, that needs are met by adult services, and that family goals drive the transition process. Issues of identity, sexuality and spiritual development require specific focus. Funding, training and improved key working need to be addressed. A multidisciplinary approach with improved access to adult respite services is vital.